To Treat Molluscum Contagiosum or Not—Curettage: An Effective, Well‐Accepted Treatment Modality. Issue 6 (7th September 2016) - Harel, Avikam; Kutz, Ana Maria; Hadj‐Rabia, Smail; Mashiah, Jacob
Abstract: Background/Objectives: Molluscum contagiosum (MC) is a common viral disease primarily affecting children. The objective was to compare the effectiveness of curettage as a treatment modality for MC with no treatment. Methods: We performed a retrospective study of 2, 022 children with MC between 2008 and 2012. Epidemiologic, clinical, and treatment data, including effectiveness, safety, and satisfaction, were reviewed. Results: Fifty‐six percent of the children were 2 to 5 years of age. The duration of the infection was 1 to 2 years for 51%, less than 1 year for 32%, and more than 2 years for 17% of the children. Seventy percent of the children were self‐referrals; 86% had had a previous examination and 76% of those had been advised not to treat the infection. The disease was mild (22%), moderate (64%), or severe (14%). A total of 1, 879 patients underwent curettage; 70% were cured after one treatment and 26% after two treatments. Satisfaction was high: 97% of children and parents. Conclusion: Active treatment should be offered despite the fact that MC is self‐limiting. Curettage in an appropriate setting is very effective, with high patient satisfaction and fast cure rates.